Hambatan dalam Penerapan Konstruksi Berkelanjutan pada Penyelenggaraan Infrastruktur - Adu, Markus Reinaldi Nikodemus; Messah, Yunita A.; Hangge, Elsy E.; Bolla, Margareth E. (Universitas Ibn Khaldun, 2026)
The construction industry has an important role in economic growth, but construction activities have a significant impact on the environment, so the implementation of sustainable construction is very important. This study aims to evaluate the extent of the application of sustainable principles in infrastructure implementation in East Nusa Tenggara Province and identify the main obstacles. The data collection method used questionnaires and interviews with 33 Commitment Making Officials (PPK). The data obtained was analyzed using mean and standard deviation statistical analysis as well as content analysis to obtain the constraints. The results of the analysis show that the percentage of sustainable construction implementation in NTT is 77.32%, which is included in the predicate of